PENGARUH MODEL PROBLEM BASED LEARNING TERINTEGRASI DENGAN THINK PAIR SHARE PADA PEMBELAJARAN IPS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Solihah, Ade Putri Siti; Puspitasari, Wina Dwi; Yanto, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is a crucial skill in Social Studies education, as it enables students to understand issues, analyze information, provide reasoning, and draw conclusions. This study aimed to determine the impact of the Problem-Based Learning model integrated with Think-Pair-Share on students' critical thinking skills in Social Studies. A quantitative approach using a quasi-experimental method was employed. The study subjects consisted of 44 fourth-grade students from SDN Jatipamor 1, divided into an experimental group (22 students) and a control group (22 students). The experimental group received instruction using the Problem-Based Learning model integrated with Think-Pair-Share, while the control group used the standard Problem-Based Learning model. The instructional material focused on buying and selling activities as a means of meeting needs. Data were collected via an eight-item essay test on critical thinking skills, administered both before and after instruction. Data analysis was conducted using Paired Sample t-Tests and Independent Sample t-Tests at a significance level of 0.05. The results revealed a difference in students' critical thinking skills before and after the implementation of the Problem-Based Learning model integrated with Think-Pair-Share. The mean score increased from 49.23 in the pretest to 64.86 in the posttest, with a significance value of < 0.001. The Independent Sample t-Test results also indicated a significant difference between the experimental and control groups, with mean posttest scores of 64.86 and 50.32, respectively, and a significance value of 0.024. Thus, the Problem-Based Learning model integrated with Think-Pair-Share influences students' critical thinking skills in Social Studies.